2020
DOI: 10.1177/0093854820913311
|View full text |Cite
|
Sign up to set email alerts
|

Examining Change in Family Conflict and Family Violence After Release From Prison

Abstract: This study examines changes in family conflict and violence among a sample of adult men after release from prison. Using longitudinal panel data on 1,282 men in the Serious and Violent Offender Reentry Initiative, cross-lagged dynamic fixed-effects panel data models are used to examine factors that relate to family conflict and family violence perpetrated by men after release from prison. Increased contact with family members during incarceration, as well as postrelease family support, related to decreased fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Studies of samples who all experienced incarceration (Freeland Braun, 2012; McKay et al, 2018a; 2018b; Stansfield et al, 2020) all focused on incarcerated men (regardless of prior offense category) and testing whether the releasee perpetrated any new family violence, broadly defined. The one exception was a recent study by Mowen and Fisher (2019) that used a sample of juveniles within the Serious and Violent Offender Reentry Initiative (SVORI) data to examine new family violence incidents perpetrated by juveniles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of samples who all experienced incarceration (Freeland Braun, 2012; McKay et al, 2018a; 2018b; Stansfield et al, 2020) all focused on incarcerated men (regardless of prior offense category) and testing whether the releasee perpetrated any new family violence, broadly defined. The one exception was a recent study by Mowen and Fisher (2019) that used a sample of juveniles within the Serious and Violent Offender Reentry Initiative (SVORI) data to examine new family violence incidents perpetrated by juveniles.…”
Section: Resultsmentioning
confidence: 99%
“…Possible responses ranged along a 6-point scale (0 = never , 1 = once , 2 = a few times , 3 = about once a month , 4 = a couple of times a month , 5 = once a week , and 6 = several times a week ). For the 1,282 former violent offenders in Stansfield and colleagues’ (2020) analysis of the SVORI data, the frequency of family violence postrelease was reported, with an average of 1.4 corresponding to between “once” and “a few times.” It is worth noting that the preincarceration prevalence of family violence in that study corresponded to about “once a week.” Given the reduction in occurrence, the authors caution that this could be a relatively low count based on people underreporting family violence in follow-up interviews, but the average is consistent with the other existing datasets that include pre- and postincarceration family violence. One of these datasets is the Returning Home study (Yahner & Visher, 2008), which finds similar trends in family violence whereby postrelease family violence levels (reported by 10% of individuals) are significantly lower than preincarceration family violence (29%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, consistent with prior research utilizing the SVORI data, we include a series of variables related to the individual's criminal and correctional history (see, for example, Alward et al, 2020;Mowen et al, 2020;Stansfield et al, 2020). Given that previous research has found criminal and correctional history variables to be predictive of reentry outcomes (Makarios et al, 2010;Spivak & Damphousse, 2006), we include these measures to explore their potential influence on the supervision relationship.…”
Section: Independent Variables: Individual Characteristic Variablesmentioning
confidence: 99%